2011
DOI: 10.1002/pbc.22956
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density is normal in children with Fanconi anemia

Abstract: Children and adolescents with FA have normal BMD prior to and after HCT, when DXA results are adjusted for bone size/height age. In contrast, BA-adjustment of BMD was not useful in this population. Individual BMD results may be influenced by gonadal function, transplantation status, and prolonged glucocorticoid therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…Patients with FA were shown to have low BMD, more so after hematopoietic stem cell transplantation . Given FA patients’ short stature, some argue that correction for height‐age is required for patients with FA, which eliminates the prevalence of low BMD . Various factors may also contribute to differences between studies with patients affected by FA, including age, treatments, and hypogonadism; as such, using mouse models with identical genetic background would at least eliminate some of these variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with FA were shown to have low BMD, more so after hematopoietic stem cell transplantation . Given FA patients’ short stature, some argue that correction for height‐age is required for patients with FA, which eliminates the prevalence of low BMD . Various factors may also contribute to differences between studies with patients affected by FA, including age, treatments, and hypogonadism; as such, using mouse models with identical genetic background would at least eliminate some of these variables.…”
Section: Discussionmentioning
confidence: 99%
“…(7,9) Given FA patients' short stature, some argue that correction for height-age is required for patients with FA, which eliminates the prevalence of low BMD. (6,7) Various factors may also contribute to differences between studies with patients affected by FA, including age, treatments, and hypogonadism; as such, using mouse models with identical genetic background would at least eliminate some of these variables. In our study, we used two different mouse models of FA, FancA -/and FancC -/-, and found growth and mineralization delays in all bones throughout development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only other study reported in the literature that focused on BMD exclusively in FA patients was a cross-sectional analysis of LBMD (but not TBMD) in 37 FA patients (aged 4-23 years, 19 without HCT and 18 post-HCT) [12]. While about 50% of these FA children had LBMD Z-scores for chronological age below −1 SD, most patients had normal BMD when adjusted for height.…”
Section: Discussionmentioning
confidence: 99%
“…Although many of these risk factors are prevalent in FA patients [3, 4, 10, 11], bone health in the FA population is poorly understood. Only two published studies have addressed BMD in children with FA [9, 12], both using DXA. However, it remains unclear to what extent children with FA manifest BMD deficits after HCT, to what degree DXA results are impacted by short stature in this patient population, and which skeletal sites are most informative.…”
Section: Introductionmentioning
confidence: 99%